Does the way we do science foster discovery? - Sivadas, Nithin (Frontiers in Astronomy and Space Sciences, 2023)
Freedom to explore the unknown is key to scientific discovery. Maximizing modern individualistic measures of scientific productivity like citations and number of publications may impede the progress of science as a whole.